Rapid Fabrication of Cell-Laden Microfibers for Construction of Aligned Biomimetic Tissue - Lu, Bingchuan; Li, Mingfeng; Fang, Yongcong; Liu, Zibo; Zhang, Ting; Xiong, Zhuo (Frontiers in Bioengineering and Biotechnology, 2021)
Bottom-up engineering of tissue constructs is being rapidly developed and broadly applied in biomanufacturing. As one type of building block, cell-laden microfibers are promising for reconstruction of oriented structures and functions of linear tissues, such as skeletal muscles, myocardia, and spinal cord tissues. Herein, we propose wet-spinning method with agitating collection, wherein alginate-based material is extruded into an agitated CaCl2 bath with a magnetic rotor acting as the microfiber collector. By applying this method, we achieve rapid fabrication and oriented collection of hydrogel microfibers. In addition, we encapsulate myoblasts in the hydrogel to form cell-laden microfibers, which show a high viability during in vitro culture. Moreover, the method allows to fabricate of cell-laden core–sheath microfibers and hollow microfibers. We also fabricate 3D constructs using various methods of microfiber assembly, namely, bundling, weaving, and braiding. The assembling results suggest that the proposed method is a promising technology for bottom-up engineering of aligned biomimetic tissue constructs.